2011
DOI: 10.5535/arm.2011.35.6.844
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Risk Factors for Refracture after Percutaneous Vertebroplasty

Abstract: ObjectiveTo identify risk factors for developing a vertebral refracture after percutaneous vertebroplasty.MethodA retrospective analysis of 60 patients who had undergone percutaneous vertebroplasty between January 2008 and April 2010 was conducted. All patients were observed for a 1 year follow-up period, and fracture was defined when it was both clinically reported and radiographically confirmed. Twenty-seven patients with a refractured vertebra and 33 patients without a refracture were included. Of the 60 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 20 publications
6
37
0
Order By: Relevance
“…However, as with the three cases reported here, the cemented vertebrae can recollapse after PV 10 12 13 16 22 23. Regarding the risk factors for this complication, Kang et al 23 suggested that a higher preoperative local kyphotic angle and a higher sagittal index24 may result in refracture, based on a comparison of patients with or without refracture. Chen et al 16 demonstrated that an MRI finding of preoperative osteonecrosis and a relatively large postoperative restoration of anterior vertebral height without a corresponding correction in the kyphotic angle increased the risk of refracture.…”
Section: Discussionsupporting
confidence: 53%
“…However, as with the three cases reported here, the cemented vertebrae can recollapse after PV 10 12 13 16 22 23. Regarding the risk factors for this complication, Kang et al 23 suggested that a higher preoperative local kyphotic angle and a higher sagittal index24 may result in refracture, based on a comparison of patients with or without refracture. Chen et al 16 demonstrated that an MRI finding of preoperative osteonecrosis and a relatively large postoperative restoration of anterior vertebral height without a corresponding correction in the kyphotic angle increased the risk of refracture.…”
Section: Discussionsupporting
confidence: 53%
“…After reviewing the full text of the remaining 26 studies, we excluded nine additional full‐text articles. Finally, 17 unique studies with sufficient data were included and analysed in the meta‐analysis . A flow diagram that shows the literature search process is presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, prior studies have investigated many of the risk factors for the development of new VCFs following vertebroplasty, such as low body mass index (BMI), intradiscal cement leakage, high cement volume, low bone mineral density (BMD) and multiple vertebral levels affected . However, these studies were limited by either a small sample size or a limited number of potential risk factors investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Factors related to PVP procedures include intradiscal leakage 8,13 and cement distribution. 14 It has also been hypothesized that factors such as the presence of Z2 preexisting vertebral compression fractures 11 and a high preoperative local kyphotic angle and sagittal index 15 affect refracture after PVP.…”
mentioning
confidence: 99%